Grund, Gestalt und Bestimmung der Kirche: Potenziale eines ökumenischen Lernprozesses in der Ekklesiologie - Nüssel, Friederike (Catholica <Münster>, 2022)
This paper discusses the ecdesiological insights gained in the consultation on church and church fellowship between representatives of the Community of Protestant Churches in Europe (CPCE) and the Pontifical Council for Promoting Christian Unity. In the introduction, the formation of this conversation and its significance for the ecumenical movement in Europe is discussed. Then the approach in the understanding of the church is reflected on the differentiation of the foundation, shape and mission of the church, which proceeds from the implicit reference of the CPCE church study to the understanding of the church in Lume n Ge n tium. The explication is an ecumenical learning process that points the way for further conversations on ecclesiology.
Keywords: Die Kirche Jesu Christi; Vatikanisches Konzil <Vatikanstadt> / Lumen gentium; Kirchengemeinschaft; Interkonfessionelles Gespräch; Ekklesiologie; Gemeinschaft Evangelischer Kirchen in Europa; Katholische Kirche